The Epistemological Interpretation of Truth in Sh.Perperyan’s Evaluative Views - Karapetyan, Vardan (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The article is devoted to the epistemological views of the Armenian philosopher, thinker Sh. Perperyan, in particular, the problem of truth in the context of axiological analysis. The article discusses issues related to forms of cognition, peculiarities of worldview, essence, nature, types of truth and a number of other epistemological problems. The article analyzes the axiological, epistemological ideas of Perperyan. An attempt is made to reveal the relationship between humans and truth, the process of evaluating the truth. Issues related to the problem of truth such as the existence of truth, the possibility of achieving it, the causes and the importance of striving for truth are discussed through comparative analysis.
Keywords: Art